Analgesic and anti-Inflammatory activity of Tradescantia fluminensis leaves extract - Rwai Waweru, Wilson; Obado Osuwat, Lawrence; Wambui Mureithi, Connie (My University, 2017)
The present study sought to evaluate the anti-inflammatory and analgesic activities of ethanolic extract from Tradescantia fluminensis leaves. Methods: The crude leaf extract of T. fluminensis was investigated for anti-inflammatory and analgesic activities in Wistar Albino rats and mice respectively. The anti-inflammatory activity was investigated using egg albumin induced oedema model while acetic acid and formalin-induced paw licking models were used to evaluate the analgesic activity. Results: The extract showed a significant (P<0.05) dose-dependent inhibition of inflammation and pain compared to the control group. Conclusion: The leaf extract possesses anti-inflammatory and analgesic activities. The activities could be attributed to phytochemicals present in the plant.
Keywords: Tradescantia fluminensis; Analgesic activity; Anti-inflammatory activity